Basic documents on human rights - "Brownlie, Ian ed." (Oxford, 1981)
The object of this work is to provide a useful collection of sources on human rights in the form of a handbook. Omission of items included in the first edition has been necessary in order to make room for certain significant materials which have emerged in recent years. The items excluded are the documents relating to fundamental rights in national legal systems and the Proclamation of Tehran. The new appearances include the Final Act of the Helsinki Conference , the United Nations Declaration on Protection from Torture and the judgement of the European Court on Human Rights in the Sunday Times case.
Keywords: Civil Rights History Sources